Seismic anisotropy of sandstone aquifers in coal seam roofs - Hang YU; Tongjun CHEN (Meitian dizhi yu kantan)
ObjectiveThe identification and assessment of sandstone aquifers in coal seam roofs play a vital role in the safe mining of mines. Investigating the rock physics and amplitude variation with incidence and azimuth (AVAz) responses of these sandstone aquifers is critical to the prevention and control of water hazards in mines. MethodsBy integrating rock physical models Voigt-Reuss-Hill (VRH), differential equivalent medium (DEM), Hudson, and Wood, as well as Gassmann’s anisotropic fluid substitution theory, this study proposed a rock physics modeling method for fractured sandstones of the horizontal transversely isotropic (HTI) media type (hereafter referred to as HTI sandstones). Using this method, this study explored the impacts of fracture parameters and water saturation on seismic rock physical responses of the sandstones. Accordingly, it constructed a two-layer theoretical forward model, calculated the reflection coefficients of HTI sandstones, and analyzed the relationships of the reflection coefficients with the fracture density and water saturation. Results and Conclusions The rock physics modeling results indicate that a higher fracture density corresponded to lower compressional and shear wave (also referred to as P- and S-wave) velocities and stronger anisotropy. As the water saturation increased, the P-wave velocity decreased initially and then increased, whereas the S-wave velocity decreased slightly. Concurrently, with an increase in the water saturation, anisotropy coefficients \begin{document}$ {ε ^{({\text{v}})}} $\end{document} and \begin{document}$ {δ ^{({\text{v}})}} $\end{document} increased, while anisotropy coefficient \begin{document}$ {γ ^{({\text{v}})}} $\end{document}remained unchanged. The AVAz forward modeling results indicate that a higher fracture density was associated with more pronounced azimuthal anisotropy of the sandstones’ reflection coefficients and larger differences in P-wave reflection coefficients between saturated and dry sandstones. The saturation state of sandstones was the most distinguishable in the case where the angle of incidence and azimuth were 40° and 0°, respectively. Indicators for sensitivity to the fracture density and water saturation of sandstone aquifers included the fitted slope and intercept of the AVAz curves, as well as the isotropic and anisotropic components of the amplitude versus offset (AVO) gradients. The results of this study provide a theoretical basis for the identification and assessment of sandstone aquifers.